Flood Water Level Simulation Bringin River, Semarang City By Using The HEC-RAS 6.3.1 Programming - satria perdana, ananda; sejati, wahyu (Pandawan, 2023)
The Bringin River is a river in West Semarang, Semarang City, with the Tugu Region drainage subsystem. The Bringin watershed covers parts of the area in Tugu District, Ngaliyan District, and Mijen District. The overflow of water caused by high rainfall resulted in river flooding. The cross-section of the Bringin River cannot accommodate the magnitude of the flood discharge. The purpose of this study was to determine the cross-section of the Bringin River which was experiencing an overflow by carrying out a Hydrological Analysis and using the HEC-RAS 6.3.1 Program as a 1-dimensional cross-sectional design. Calculation of the planned flood discharge with periods of 2, 5, 10, 25, and 50 years using the Nakayasu Synthetic Unit Hydrograph method with a peak discharge Q2years : 52.45 m3/second, Q5years : 62.43 m3/second, Q10years: 68.44 m3/second, Q25years : 75.09 m3/second, and Q50years : 79.95 m3/second. The results of the calculation of the design discharge will be used in the HEC-RAS 6.3.1 programming so that from these results it can be seen that several cross-sections of the river have flood overflows that exceed the capacity of the Bringin River under review.